A Critical Analysis of Bano Qudsia’s short story "Black Drongo" in the Context of Racial Discrimination - Dr. Ghulam Farida; Dr. Tahir Nawaz; Dr. Maria Termezi (Al-Qanṭara, 2024)
Critical race theory is an interpretive approach that intends to unfold the deeper and underlying meanings of the color discrimination or racism and provides a methodology to understand the racism, history, and related discriminative elements. The general meaning of racism is to divide people into different groups based on their biological makeup. According to this theory, people living in different regions have their hereditary structure or appearance, skin, hair, eye color, shape of eyelids, nose and have different identity from the people living in other regions. Richard Delgado and Jean Stefancic are known as key figures of critical race theory (CRT). Bano Qudsia, female writer has significance in the history of Urdu short story writing. Her short story "Black Drongo" is written in the post-colonial period of the sub-continent. The main theme of this fiction is social discrimination based on color. This article is a critical analysis of the short story “Black Drongo” in the context of racial discrimination.